The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/acps.13557
|View full text |Cite
|
Sign up to set email alerts
|

Association between childhood maltreatment and social functioning in individuals with affective disorders: A systematic review and meta‐analysis

Abstract: Objective: Childhood maltreatment has been linked to impairments in social functioning and social cognition in adults with affective disorders. However, conclusions have been limited by inconsistent findings across different maltreatment subtypes and social domains. We conducted a systematic review and meta-analysis to quantify associations between childhood maltreatment (overall and subtypes -physical, emotional and/or sexual abuse, and/or physical and/or emotional neglect) and different domains of social fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 183 publications
2
16
0
Order By: Relevance
“…The correlations were moderate with depressive and weak with (hypo)manic symptoms, probably because these items explore the regulation of negative emotions, as mentioned earlier. Risk behaviors are in fact a core symptom of mania 39 and, importantly, they are also related to aggressive behaviors, 86 mediated by common factors such as affective temperaments 87,88 or childhood maltreatment 89,90 . Indeed there is evidence that risk‐taking was dependent on current mood status, as scores were highest in people with BD who were currently manic compared to those who were currently depressed or euthymic 91,92 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlations were moderate with depressive and weak with (hypo)manic symptoms, probably because these items explore the regulation of negative emotions, as mentioned earlier. Risk behaviors are in fact a core symptom of mania 39 and, importantly, they are also related to aggressive behaviors, 86 mediated by common factors such as affective temperaments 87,88 or childhood maltreatment 89,90 . Indeed there is evidence that risk‐taking was dependent on current mood status, as scores were highest in people with BD who were currently manic compared to those who were currently depressed or euthymic 91,92 …”
Section: Discussionmentioning
confidence: 99%
“…Risk behaviors are in fact a core symptom of mania 39 and, importantly, they are also related to aggressive behaviors, 86 mediated by common factors such as affective temperaments 87,88 or childhood maltreatment. 89,90 Indeed there is evidence that risk-taking was dependent on current mood status, as scores were highest in people with BD who were currently manic compared to those who were currently depressed or euthymic. 91,92 Negative focus strategy, defined as over-emphasizing the negative aspects of an experience and predicting the worst possible outcome, and focusing on self-critical thoughts, blaming self or others for events/situations that are not the complete responsibility of the individual, 3 also appeared to be correlated positively with both polarities of BD.…”
Section: Discussionmentioning
confidence: 99%
“…Both cognitive (Büetiger et al, 2023; Popovic et al, 2019; Velikonja et al, 2021) and psychosocial functioning (Christy et al, 2023; Fares-Otero, Alameda, et al, 2023; Fares-Otero, De Prisco, et al, 2023; Tzouvara et al, 2023) are implicated in the sequelae of CM and are transdiagnostic mechanisms in the development of psychopathology (McLaughlin et al, 2020). Our exploratory analyses provide insight into understanding the nuances of this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence supports that childhood maltreatment increases the risk of mood disorders substantially. 8,9 In addition, childhood maltreatment is associated with an earlier age at onset of mood disorder, a more severe illness course, impaired social functioning 10 including cognitive difficulties, 11 more perceived stress, lower quality of life, 12 sexual health problems, 13,14 and physical diseases. 15,16 The landmark study by Caspi et al 17,18 showed that the impact of severe life events seems mediated through genetic variation, variations that contributed to an increased vulnerability in maltreated children.…”
Section: Introductionmentioning
confidence: 99%